On minimal prime ideals of commutative Bezout rings - Gatalevych, A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study the spectrum of minimal prime ideals of commutative Bezout rings. We apply the results obtained to the problem of diagonal reduction of matrices over rings of this sort.